2013
DOI: 10.1063/1.4804677
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of size and electronic effects on Kapitza conductance with non-equilibrium molecular dynamics

Abstract: In nanosystems, the thermal resistance between materials typically dominates the overall resistance. While size effects on thermal conductivity are well documented, size effects on thermal boundary conductance have only been speculated. In response, we characterize the relationship between interfacial resistance and material dimension using molecular dynamics. We find that the interfacial resistance increases linearly with inverse system length but is insensitive to cross-sectional area. Also, from the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 47 publications
9
56
3
Order By: Relevance
“…Generally speaking, domain length can have a significant influence on the thermal conductivities predicted by NEMD simulations due to the fact that the fixed ends of the domain serve as phonon scattering sites, thereby shortening mean-free-paths and reducing observed thermal conductivities [129,205,206]. However, we do not observe any statistically significant change in the predicted thermal conductivities of amorphous Si or the amorphous SLs (see comparison in Fig.…”
Section: Thermal Boundary Resistance and Thermal Conductivity Of Amorcontrasting
confidence: 44%
See 1 more Smart Citation
“…Generally speaking, domain length can have a significant influence on the thermal conductivities predicted by NEMD simulations due to the fact that the fixed ends of the domain serve as phonon scattering sites, thereby shortening mean-free-paths and reducing observed thermal conductivities [129,205,206]. However, we do not observe any statistically significant change in the predicted thermal conductivities of amorphous Si or the amorphous SLs (see comparison in Fig.…”
Section: Thermal Boundary Resistance and Thermal Conductivity Of Amorcontrasting
confidence: 44%
“…The inclusion of these interfaces gives rise to both phononboundary scattering, effectively reducing the thermal conductivity of the solid due to classical size effects [128], and/or partial transmission of thermal energy across the interface driving the thermal boundary conductance [21,22]. To atomistically manipulate the phonon thermal conductivity of a nanosystem with a high density of material interfaces, an understanding of the interplay and relationship of phonon-boundary scattering and thermal boundary conductance across the interfaces must be understood; it is important to note that the reduction in the thermal conductivity of a material due to phonon boundary scattering may not be entirely correlated to the intrinsic thermal boundary conductance between two solids, and is influenced by ballistic transport and phonon mean free paths incident upon the interface, as has been shown both computationally [129] and experimentally [4]. Given that the structural and chemical properties of solid interfaces can strongly influence the thermal boundary conductance [13], the ballistic or diffusive nature of phonon transport, along with the corresponding phonon wavelengths [125], can affect how energy is scattered and/or transmitted across an interfacial region between two materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that by including the e-ph effect, interfacial thermal conductance is significantly reduced. Jones et al 14 and…”
Section: / 23mentioning
confidence: 99%
“…14,15 Copper has a much smaller e-ph coupling factor (g=0.5×10 17 W/m 3 K) and a larger electron thermal conductivity than those of aluminum (g=2.4×10 17 W/m 3 K), 22 respectively. According to Fig.…”
Section: / 23mentioning
confidence: 99%
“…31 A modified Tersoff potential based on a parameterization by Porter et al 32 was employed to describe the interactions between Si and C atoms, whereas dopant/dopant and dopant/matrix (i.e., Si and C atoms) interactions were described, for simplicity, by a shifted Lennard Jones (LJ) potential. 11,12,30,[33][34][35] The LJ interaction captures generically some of the anharmonic effects that govern phonon scattering and, thereby, thermal transport properties. While the length parameter, σ, and energy parameter, ε dd, , for dopant/dopant interactions were kept constant at 2.0 Å and 0.3 eV, respectively, the energy parameter, ε dm, , for dopant/matrix interactions (with either Si or C) was constrained on the interval 0.03 eV ≤ ε dm ≤ 0.3 eV.…”
Section: A Computational Modelmentioning
confidence: 99%